2017
DOI: 10.1016/j.fertnstert.2016.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Accurate quantitation of mitochondrial DNA reveals uniform levels in human blastocysts irrespective of ploidy, age, or implantation potential

Abstract: We recommend implementation of the correction factor calculation to laboratories evaluating mtDNA levels in embryos by NGS or qPCR. When applied to our in-house data, the calculation reveals that overall levels of mtDNA are largely equal between blastocysts stratified by ploidy, age, or implantation potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
112
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(119 citation statements)
references
References 29 publications
6
112
1
Order By: Relevance
“…However, in this study we did not observe any correlation between maternal age (24-46 years) at the time of oocyte retrieval and mtDNA levels in trophectodermal cells of blastocyst. Similar to our findings, other studies also failed to report any correlation between maternal age with mtDNA levels in the blastocysts (de Los Santos et al, 2018; Diez-Juan et al, 2015; Klimczak et al, 2018; Victor et al, 2017). Together the results indicate, maternal age does not contribute to alterations in mtDNA levels in the blastocysts.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, in this study we did not observe any correlation between maternal age (24-46 years) at the time of oocyte retrieval and mtDNA levels in trophectodermal cells of blastocyst. Similar to our findings, other studies also failed to report any correlation between maternal age with mtDNA levels in the blastocysts (de Los Santos et al, 2018; Diez-Juan et al, 2015; Klimczak et al, 2018; Victor et al, 2017). Together the results indicate, maternal age does not contribute to alterations in mtDNA levels in the blastocysts.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, in another study, embryos with monosomies showed higher mtDNA levels as compared to embryos trisomies (de Los Santos et al, 2018). Whereas, some studies fail to show any association between chromosomal status of the blastocyst and mtDNA levels (Qui et al, 2018; Victor et.al., 2017). The association of mtDNA levels and the ploidy status of the blastocyst require further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While these data support the conclusion that mtDNA may serve as a useful biomarker of reproductive potential, multiple questions still remain with regards to the clinical applicability of this technology. In addition, another group recently reported the lack of predictive value of mtDNA for reproductive potential using a modified methodology that improved normalization strategies (Victor et al ., 2016). …”
Section: Introductionmentioning
confidence: 99%
“…According to the "quiet embryo" hypothesis, under ideal circumstances, embryos are in low metabolic activity, which suggests that a viable embryo has a relatively lower metabolism, whereas those under stress and of reduced developmental potential, tend to be metabolically more active (Ravichandran et al, 2017). Elevated mtDNA levels and by extension increased adenosine triphosphate (ATP) production could be a compensatory mechanism providing distressed embryos with more chemical energy to overcome adverse conditions (Victor et al, 2017). MtDNA replicates since the primordial germ cell stage and the MII oocyte fixes its mtDNA composition before fertilization (St. John, 2014).…”
Section: Discussionmentioning
confidence: 99%